DDA1, a novel oncogene, promotes lung cancer progression through regulation of cell cycle. Issue 8 (17th February 2017) - Cheng, Lin; Yang, Qianmei; Li, Can; Dai, Lei; Yang, Yang; Wang, Qingnan; Ding, Yu; Zhang, Junfeng; Liu, Lei; Zhang, Shuang; Fan, Ping; Hu, Xun; et al.
Abstract: Lung cancer is globally widespread and associated with high morbidity and mortality. DDA1 (DET1 and DDB1 associated 1) was first discovered and registered in the GenBank database by our colleagues. DDA1, an evolutionarily conserved gene, might have significant functions. Recent reports have demonstrated that DDA1 is linked to the ubiquitin–proteasome pathway and facilitates the degradation of target proteins. However, the function of DDA1 in lung cancer was previously unknown. This study aimed to investigate whether DDA1 contributes to tumorigenesis and progression of lung cancer. We found that the expression of DDA1 in normal lung cells and tissue was significantly lower than that in lung cancer and was associated with poor prognosis. DDA1 overexpression promoted proliferation of lung tumour cells and facilitated cell cycle progression in vitro and subcutaneous xenograft tumour progression in vivo . Mechanistically, this was associated with the regulation of S phase and cyclins including cyclin D1/D3/E1. These results indicate that DDA1 promotes lung cancer progression, potentially through promoting cyclins and cell cycle progression. Therefore, DDA1 may be a potential novel target for lung cancer treatment, and a biomarker for tumour prognosis.